'True man': the true economic man for Islamic economics - Mohd, Mahyudi (Kolej Islam Darul Ridzuan, Perak, 2015)
As value-free economics is under serious attacks, Islamic economics seems to have a bright future. Unfortunately, Islamic economics is facing an identity-crisis. This paper seeks to perform an inspection on the conceptualization of the ‘Islamic economic man’ by employing a discursive method. This paper first provides a reality-check exercise which reveals that Islamic economics institution’s weak social performance originates from the absence of homo Islamicus. Thence, this paper searches for a universal truth about Muslims as economic agents. Surprisingly, this paper has found that they are neither homo Islamicus nor homo economicus. Thus, the most important implication of this paper is the replacement of homo Islamicus as the basis of the micro-foundation for Islamic economics. Instead, the concept of ‘true man’ is proposed. Therefore, future research may develop the specific details of this ‘true man’ for Islamic economics to be a more reliable social science.